Historia przebiegu ubezpieczenia w świetle unijnych dyrektyw komunikacyjnych i regulacji krajowych poszczególnych państw członkowskich - Monkiewicz, Marek (Third Party Liability Claims in the Light of the EU Motor Insurance Directives and National Regulations in Certain Member States, 2008)
The history of introducing motor insurance directives clearly shows that the main EU legislator's interest concerns consumers protection rights usually in order to prevent injured parties damaged in traffic accidents. Also the last (so far) Fifth Motor Insurance Directive (2005/14/EC) contains mainly adopted mechanisms directly relating to compensatory activity of certain institutions (insurance undertakings, guarantee funds, compensation bodies, and information centres), however there are also some provisions regulating other non-compensatory aspects of consumer protection. One of them is the certificate of TPL claims (in other words simply driving history/record). According to the intention of EU regulator any person wishing to take out new motor TPL insurance contract with another insurer should be in a position to justify his accident or claims record under the old contract. Due to the fact that aforementioned provision (as the whole directive excluding minimum guarantee sum limits) has to be implemented into Member States' national legislation via publication of relevant legislative or administrative acts no later than 11th of June 2007. The author tries to present Polish legislator's regulations applied in order to meet EU requirements also in this sphere.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2008; nr 1197, s. 279-285